2014
DOI: 10.1371/journal.pone.0093810
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Akt/NF-κB Pathways in the HTNV-Mediated Increase of IL-6, CCL5, ICAM-1, and VCAM-1 in HUVECs

Abstract: BackgroundHantaan virus (HTNV) infection causes a severe form of HFRS(hemorrhagic fever with renal syndrome)in Asia. Although HTNV has been isolated for nearly forty years, the pathogenesis of HFRS is still unknown, and little is known regarding the signaling pathway that is activated by the virus.Methodology/Principal FindingsCardamonin was selected as a NF-κB inhibitor, and indirect immunofluorescence assays were used to detect the effect of cardamonin on HTNV-infected HUVECs. The effect of cardamonin on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 58 publications
0
18
0
3
Order By: Relevance
“…It was reported that the PI3K/Akt pathway might play important roles in modulating IL-6 release in various cells [16, 17]. Thus, we examined whether Akt activation increased IL-6 expression in human lung epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the PI3K/Akt pathway might play important roles in modulating IL-6 release in various cells [16, 17]. Thus, we examined whether Akt activation increased IL-6 expression in human lung epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…IL-33 is a selective activator and preferentially targets nonquiescent HUVECs [ 11 ]. Previous reports have demonstrated that HTNV infection could induce increased levels of VCAM-1 and ICAM-1 in HUVECs [ 39 ], which could drive HUVECs into the nonquiescent state. Therefore, we hypothesised that HTNV infection activated HUVECs, causing them to become nonquiescent cells, which then became the target cells for IL-33.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, IL-33 could augment its pro-inflammatory function. Furthermore, HTNV infection could activate the NF-κB pathway in HUVECs [ 7 , 39 ]. Acting as cross-talk between HTNV and IL-33, the NF-κB pathway was highly activated when the HUVECs were treated with both HTNV and IL-33 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were used within passage 10 after primary culture. HTNV strain 76-118 was cultured in Vero E6 cells (ATCC Cat# CRL-1586, RRID:CVCL_0574) in our laboratory and titrated using an immunofluorescence staining assay for HTNV nucleocapsid protein (NP) as previously described (22). The TCID50 was 10 5 /ml, which was calculated using the Reed-Muench method.…”
Section: Cells Virus and Ifn-α2amentioning
confidence: 99%